(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
In this paper, rhinoceros remains from Apulian sites of the late Pleistocene have been analysed. The majority of these remains have been attributed to Rhinoceros mercki by several previous authors and later to Stephanorhinus kirchbergensis. The results of our analysis show how the remains are all referable to S. hemitoechus. This species, with the exception of Coelodonta antiquitatis, represent the only rhinoceros species occurring in Apulia from approximately 100.000 to 40.000 years BP. Furthermore, the considered specimens are relatively smaller than those referred to S. hemitoechus from several late Pleistocene European sites. However, the small size of the Apulian rhinoceroses seems not to be accompanied by variation in proportions and morphology. We propose that the presence of these small-sized rhinoceroses can be due to a weak effect of endemism, related to the geographic characteristics of Apulia.